THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP, HR COMPETENCE, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT THE BPKAD OFFICE OF LANGKAT REGENCY - Azzahra Chairani; Sullaida; Nur Faliza; Yusniar (PT. Radja Intercontinental Publishing, 2026)
This study aims to analyze the influence of transformational leadership, human resource competency, and organizational commitment on employee performance at the Langkat Regency BPKAD Office. The independent variables studied include transformational leadership, human resource competency, and organizational commitment, while the dependent variable is employee performance. Primary data was collected through questionnaires distributed to 82 employees at the Langkat Regency BPKAD using a saturated sampling technique. The analysis method used was multiple linear regression. The results indicate that transformational leadership, human resource competency, and organizational commitment partially have a positive and significant effect on employee performance. Furthermore, these three variables simultaneously also significantly influence employee performance at the Langkat Regency BPKAD. This study provides an important contribution to understanding that improving leadership quality, human resource competency, and organizational commitment are factors that can improve employee performance, thereby supporting the effective achievement of organizational goals.